CONSUMO DE SÓDIO NA POPULAÇÃO IDOSA DA ÁREA URBANA DE IJUÍ - WENDLAND, ROBERTA; JESUS, TATIANA D.; TUSSET, JOSIANE; MACHADO, LUCIELE; WERLE, JAMILE D. M.; SCHWEIGERT, INGRID D.; DALLEPIANE, LOIVA B.; BELLÉ, TÂNIA R. L. (Salão do Conhecimento, 2013)
Resumo